(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This study presents a comprehensive physicochemical analysis of soil samples collected from onion cultivation areas in Shirala Tahsil. The aim of the research is to assess the soil characteristics and provide valuable insights for optimizing onion cultivation practices in the region.Soil samples were collected from multiple locations, considering variations in topography, land use, and onion farming practices. The following physicochemical parameters were analyzed: soil texture, pH, electrical conductivity (EC), organic matter content, nitrogen, phosphorus, potassium, and micronutrient levels. The analysis was conducted using standard laboratory procedures and equipment.The results reveal diverse soil textures across the sampled areas, ranging from loamy to clayey soils. The pH levels varied within the slightly acidic to neutral range. Electrical conductivity values reflected the salinity status of the soil. Organic matter content exhibited variations indicative of different soil management practices. Nitrogen, phosphorus, and potassium levels were determined to assess the soil fertility status. Micronutrient analysis provided insights into the availability of essential trace elements. The findings of this study contribute to a better understanding of the soil characteristics in onion cultivation areas, offering a foundation for sustainable agricultural practices and soil management strategies. This research provides valuable information for local farmers, agricultural extension services, and policymakers to make informed decisions regarding soil amendments, fertilization, and irrigation practices in onion cultivation. The insights gained from this study are crucial for enhancing agricultural productivity and promoting sustainable farming practices in the Shirala Tahsil region.